Teaching Strategy and Learning Model Using Practice Method - Khudriyah (STIT Muhammadiyah Paciran Lamongan, 2019)
bstract : This research is done because of the phenomenon in some teaching and learning process happened at STIT al Urwatul Wutsqo. The researcher found that most of students could not practice of teaching using some methods, strategy or models. They practiced the teaching using lecturing method, mean while they are prepared to be professional teacher. The lecturing method is not bad, but it has many disadvantages, one of them is boring method, especially when the teacher cannot organize it well, the students will be bored easily. This research is aimed to know how practice method is effective to prepare the students to be professional teacher. The design of the research is qualitative descriptive, observation, questionnaire interview and documentation, were as instruments. The result is the practice method is very effective, such as; most of students were actively involved in the teaching and learning process. Most of students chose positive answer which supported the implementation of practice method, the students were able to gain good and high score, and they showed their positive responses to the teaching using practice method.